Engineered exosomes: a promising drug delivery platform with therapeutic potential - Schwarz, Genevieve; Ren, Xuechen; Xie, Wen; Guo, Haitao; Jiang, Yong; Zhang, Jinyu (Frontiers in Molecular Biosciences, 2025)
Exosomes, small membranous vesicles naturally secreted by living cells, have garnered attention for their role in intercellular communication and therapeutic potential. Their low immunogenicity, high biocompatibility, and efficient biological barrier penetration make them promising drug delivery vehicles. This review spans research developments from 2010 to 2025, covering the engineering of exosomes to optimize cargo loading and targeting specificity. We discuss their applications in treating cardiovascular diseases, liver fibrosis, immune diseases, and neurological diseases, alongside ongoing clinical trials and industry progress. Future challenges include scalability, standardization, and minimizing off-target effects. We propose strategies to address these hurdles, such as bioengineering techniques and improved isolation methods. By synthesizing current knowledge and outlining future directions, this review aims to guide researchers toward harnessing exosomes for disease treatment.